2003
DOI: 10.1021/om020699c
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Methyl Platinum Complexes in Water:  The Role of pH and Geometry

Abstract: 2 , DPPBTS), to establish the stability of the platinum methyl bond in aqueous solution. From pH ) 3 to 14 there is no reaction other than ligand substitution of H 2 O or OHfor Cl -; there is no CH 3 OH elimination. At lower pH's protonolysis of the Pt-Me bond occurs, producing CH 4 . Dissolving PtMe 2 L 2 into a solution of HCl at pH ) 1 rapidly produces PtCl 2 L 2 for the bidentate ligands, but trans-Pt(Cl)(Me)L 2 is observed for the monodentate ligands. trans-PtClMe(TPPTS) 2 undergoes protonolysis very slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…The 1 H NMR spectra of complexes 2 remained unaltered 8 days after being dissolved in D 2 O under neutral or alkaline conditions (0.1 M NaOD) at room temperature. The stability of these complexes in water resembles that found by Atwood’s group for Pt(II) dimethyl complexes with sulfonated phosphanes . In contrast, it has been reported that PtMe 2 complexes with sulfonated iminopyridine ligands are quickly degraded under similar conditions by displacement of the didentate N,N-ligand by water .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The 1 H NMR spectra of complexes 2 remained unaltered 8 days after being dissolved in D 2 O under neutral or alkaline conditions (0.1 M NaOD) at room temperature. The stability of these complexes in water resembles that found by Atwood’s group for Pt(II) dimethyl complexes with sulfonated phosphanes . In contrast, it has been reported that PtMe 2 complexes with sulfonated iminopyridine ligands are quickly degraded under similar conditions by displacement of the didentate N,N-ligand by water .…”
Section: Resultssupporting
confidence: 78%
“…Broadening of resonances was, however, observed in D 2 O for 3c and 3d . The concurrence of isomerization processes in solution is well known for other square-planar haloalkyl platinum(II) complexes. , …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…What is the origin of the trans X ligand effect on protonolysis? The trans effect on protolytic stability in trans -(R 3 P) 2 Pt­(R)­(X) systems has been previously noted by Thorn, Atwood, and ourselves . We have noted that the Pt–Me 1 J CH value for the donor phosphine complex (dmpe)­Pt­(Me)­(O 2 CCF 3 ), 126 Hz, is significantly increased to 137–139 Hz in (dfepe)­Pt­(Me)­(X) systems (X = Cl, O 2 CCF 3 , OSO 2 F), reflecting substantial carbon rehybridization in response to decreased metal electron density.…”
Section: Discussionsupporting
confidence: 64%
“…212 Aqueous solutions of a range of complexes of the form [PtMe 2 L 2 ], where L represents a range of ligands of which P(m-C 6 H 4 SO 3 Na) 3 is typical, are stable to hydrolysis of the Pt-Me bond over pH range of 3-14. 213 However, below pH 3, protonolysis yielding CH 4 becomes a feature of the reactions. The mechanism of the protonolysis the Pt(II) bonds in [PtPh(2,6-C 6 H 3 (CH 2 NMe 2 )) 2 ] and [PtPh(Bu 2 bpy)] has been determined.…”
Section: Organometallicsmentioning
confidence: 99%